2019
DOI: 10.3389/fpsyg.2019.00074
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Triggers of Alcohol Craving to Develop Effective Virtual Environments for Cue Exposure Therapy

Abstract: Background: Many studies have indicated that alcohol craving is a core mechanism in the acquisition, maintenance, and precipitation of relapse in alcohol use disorder (AUD). A common treatment approach in AUD is cue exposure therapy (CET). New technologies like virtual reality (VR) have the potential to enhance the effectiveness of CET by creating realistic scenarios in naturalistic environments. In this study, we aimed to determine relevant triggers of alcohol craving in patients with AUD.Methods: We enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 104 publications
(149 reference statements)
1
25
0
Order By: Relevance
“…We interpret this result as being representative of a group of young social drinkers, whose drinking patterns involve social interaction and peer pressure, especially in bars and pubs. The result also confirms the contextual specificity of craving for alcohol [49,54].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We interpret this result as being representative of a group of young social drinkers, whose drinking patterns involve social interaction and peer pressure, especially in bars and pubs. The result also confirms the contextual specificity of craving for alcohol [49,54].…”
Section: Discussionsupporting
confidence: 75%
“…“ALCO-VR” software was developed based on the results of a previous study [49], in which we identified factors that contribute to the elicitation of alcohol craving in a sample of patients diagnosed with AUD. Based on that study, the ALCO-VR software was created, consisting of four VR alcohol-related environments: a restaurant, a bar, a pub, and at-home environments (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…However, neurobiological changes may occur with repetitive binge-drinking conditions [31,32], and may increase cravings [33]. Ghiţă et al reported a variability of the levels of alcohol craving in relation to the day of the week, and drinking during weekends in Spain (Friday, Saturday, or Sunday) was associated with greater craving levels in patients with alcohol use disorder [17]. These ndings may support the high intake on Monday and Friday in the Burkinabe context.…”
Section: Associations Between Dependence Signs and Increased Drinkingmentioning
confidence: 91%
“…In the alcohol misuse/addiction process, dependence is the ultimate state, with craving as the main feature [12]. It has been suggested that alcohol cravings are triggered by peer pressure in social environments [13,14], that alcohol cravings are context-dependent [15,16] and that the time of the day [17] and day of the week [18,19] may modulate alcohol cravings. The relationships between weekdays and weekend drinking and alcohol misuse have not been explored in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…a bar, a pub and parties), but women also reported higher levels of cravings in contexts not commonly associated with alcohol (e.g. the workplace, bedroom and supermarket) (Ghiţă et al, 2019). Thus, alcohol craving in men may be more specific to certain environmental contexts than in women.…”
mentioning
confidence: 96%